Optimasi Konsentrasi Sukrosa dan Propilen Glikol dalam Formulasi Chewable Gummy Tablet Ekstrak Daun Kelor (Moringa oleifera L) - Karina Citra Rani; Maulidia Setaratika; Syalza Mumpuni Kusuma Dewi; Nikmatul Ikhrom Eka Jayani (BIOEDUSCIENCE, 2023)
Background: Moringa leaf extract is promising to develop into nutraceutical products, especially a chewable gummy. The desirable characteristics of chewable gummies are soft, elastic, springy and flexible. Gelatin is a widely used gelling agent which has been proven to maintain gel structure during storage. The other ingredients which also determine the chewable gel structure are fillers and plasticizers. The aim of this study was to determine the effect of sucrose and propylene glycol concentrations on Moringa leaf extract based on chewable gummy. Method: The preparation of chewable gummy tablets was carried out by the pour method. Factorial design study (22) was applied in this study to analyze the effect of two factors here in filler and plasticizer. Two levels of concentration were optimized in each factor, herein sucrose (30% and 35% concentration) and propylene glycol (2% and 4% concentration) on the physical characteristics of the gummy tablet. Result: The results of the factorial analysis showed that the increase in sucrose concentration will produce a longer dispersion time and lower swelling ratio. Meanwhile, the increase in propylene glycol decreases the syneresis potency. The alteration of physical characteristics was observed during 14 days of storage, particularly in dispersion time, swelling ratio, and syneresis percentage. Conclusion: Based on the results of a feasible design space, sucrose concentration (30-35%) and propylene glycol concentration (2-4%) were optimized in this study to produce the desirable characteristics of chewable gummy.